Design and Development of a Web-Based Boarding House Management Information System Using RAD Method - Mohamad Ilham Praditya Arifatul Nesta; Abdul Rezha Efrat Najaf; Seftin Fitri Ana Wati (bit-Tech, 2025)
The rapid growth of urban migration in Indonesia, particularly among students and workers, has increased the demand for efficient and integrated boarding house management systems. However, many boarding house businesses still rely on manual processes for tenant registration, payment tracking, and data recording, leading to inefficiencies and data inaccuracies. This study aims to design and develop a web-based boarding house management information system to optimize operational performance and enhance service quality for both owners and tenants. The system was developed using the Rapid Application Development (RAD) method, which emphasizes iterative prototyping, user involvement, and rapid feedback to ensure functional alignment with user requirements. The application was built with ReactJS for the frontend, ExpressJS for the backend, and PostgreSQL as the database, integrated with the Midtrans payment gateway to enable secure, real-time transactions. A key contribution of this study is the combination of RAD methodology with Midtrans integration, providing a scalable and user-friendly solution for small-scale property management. The system’s functionality was tested using Black Box Testing, confirming that all features operated correctly according to design specifications. The results demonstrate that the system successfully streamlines management workflows, reduces human error by 25%, and improves the user experience by reducing administrative processing time by 30%. This study contributes to the digital transformation of small-scale property management by demonstrating the feasibility of using low-cost, scalable technologies to enhance operational efficiency and service transparency.